Pengaruh Perencanaan Pelatihan, Metode Pelaksanaan Pelatihan, dan Keterlibatan Peserta terhadap Efektivitas Pelatihan Public Speaking pada Mahasiswa Generasi Z Politeknik Aceh - Carissima Yusvi Azzahra; Febyolla Presilawati; Yuslaidar Yusuf (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of training planning, training implementation methods, and participant engagement on the effectiveness of public speaking training among Generation Z students at Politeknik Aceh. The study employed a quantitative method with a causal associative approach. The population consisted of 274 students, with a sample of 73 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that, partially, training planning (Sig. = 0.029 < 0.05) and training implementation methods (Sig. = 0.038 < 0.05) had a significant effect on the effectiveness of public speaking training, while participant engagement had no significant effect (Sig. = 0.332 > 0.05). Simultaneously, the three independent variables had a significant effect on the effectiveness of public speaking training (F = 4.404; Sig. = 0.007). The coefficient of determination (R²) was 0.161, indicating that the three independent variables explained 16.1% of the effectiveness of public speaking training, while the remaining 83.9% was influenced by other factors outside the scope of this study.